Một số cải tiến trong quá trình xây dựng phủ tối tiểu - Hào, Nguyễn Xuân (Journal of Computer Science and Cybernetics, 2016)
The problem of finding the minimal cover plays an important role in the design of a relational database. In this paper, some ameliorations are proposed for reducing the complexity of the algorithm for finding a minimal cover.